Penerapan Kebijakan Green Industry Terhadap Sustainable Development Dengan Green Innovation sebagai Variabel Mediasi pada PT Samator Gas Industri Tebing Tinggi - Sitindaon, Nikson (Sekolah Tinggi Ilmu Ekonomi Bina karya, 2024)
This research is about the Implementation of Green Industrial Policy on Sustainable Development with Green Innovation as a Mediating Variable at PT Samator Gas Industri Tebing Tinggi. In this research, the approach used by researchers is a quantitative approach. Quantitative research is systematic scientific research into parts and phenomena as well as the relationships between parts of phenomena. Data analysis techniques are used to answer problems or test hypotheses that have been formulated. Data management in this research will use smartPLS software. The first hypothesis is accepted that Green Industry (X) influences Green Innovation (Z). The second hypothesis is accepted that Green Innovation (Z) influences Sustainable Development (Y). The third hypothesis is accepted that Green Industry (X) has a significant effect on Sustainable Development (Y) through Green Innovation (Z) as an intervening variable.